Design and Implementation of Time Metrology Vocabulary Ontology - Du, Mingxin; Gao, Boyong; Wang, Shuaizhe; Liu, Zilong; Xiong, Xingchuang; Luo, Yuqi (Electronics (Basel), 2024)
The advent of the digital era has put forward an urgent need for the digitization of metrology, and the digitization of metrology vocabularies is one of the fundamental and critical steps to achieve the digital transformation of metrology. Metrology vocabulary ontology can facilitate the exchange and sharing of data and is an important way to achieve the digitization of metrology vocabulary. Time metrology vocabulary is a special and important part of the whole metrology vocabulary, and constructing its ontology can reduce the problems caused by semantic confusion, help to smooth the progress of metrological work, and promote the digital transformation of metrology. Currently, the existing ontology for metrology vocabulary is primarily the MetrOnto ontology, but it lacks a systematic description of the vocabulary of time metrology. To address this issue, improve the metrology vocabulary ontology, and lay the groundwork for realizing the digital transformation of metrology, this paper takes time metrology vocabulary as the research object; proposes a classification principle that meets the inherent requirements of time transfer in the digital world; adopts the seven-step method of ontology construction to construct an ontology specialized in time metrology vocabulary, OTMV (Ontology of Time Metrology Vocabulary); and conducts an ontology consistency check, a machine-readable validation, a machine-understandable primary validation, and information retrieval validation on it. The validation results show that OTMV has correct syntactic and logical consistency and is capable of realizing machine-readable, machine-understandable, and information retrieval. The construction of this ontology provides a systematic description of the time measurement vocabulary that can address the problem of word expression of time metrology vocabulary in the digital world and lay the foundation for the digitization of our metrology vocabulary, as well as its readability, understandability, and sharing.